A first insight on the bio-functionalization mechanisms of TiO2 nanotubes with calcium, phosphorous and zinc by reverse polarization anodization - Alves, Sofia A. [UNESP]; Rossi, André L.; Ribeiro, Ana R. [UNESP]; Werckmann, Jacques [UNESP]; Celis, Jean-Pierre; Rocha, Luís A. [UNESP]; Shokuhfar, Tolou (Elsevier, 2017)
The decoration of titanium (Ti) implant surfaces with TiO2 nanotubes has emerged as a promising strategy to improve osseointegration and avoid infection. Nevertheless, it has been reported that nanotubular films are prone to peeling off from the Ti substrate due to the poor interfacial adhesion. The knowledge on the interfacial properties of such interface, although not well explored, is crucial for understanding the mechanisms behind the poor adhesion problem of these films and to further achieve an easy and effective solution to solve it. This paper is focused on the bio-functionalization of TiO2 nanotubular films with zinc (Zn) as an antimicrobial and bone healing agent, together with two major components of bone matrix, namely calcium (Ca) and phosphorous (P). The main aim is, for the first time, the thorough characterization of the interface between TiO2 nanotubes and the Ti substrate, along with the better understanding of the bio-functionalization mechanisms of TiO2 nanotubes and their influence on the interfacial features of the films. TiO2 nanotubes were successfully synthesized by two-step anodization and their bio-functionalization with Ca, P and Zn was achieved by reverse polarization anodization treatments. The in-depth characterization of the morphological and chemical features of TiO2 nanotubes was carried out along their length by scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDS), before and after bio-functionalization treatments. STEM images showed that the interface between conventional TiO2 nanotubes and Ti is non-continuous due to the existence of a hollow space. However, bio-functionalized TiO2 nanotubes evidenced an interface with different features, due to the formation of an interfacial oxide film as a consequence of anodization, with a thickness comprised between 230 and 250 nm. The results presented in this work may inspire the emergence of novel surface treatment strategies seeking the long-term performance of metallic-modified osseointegrated implants.
Keywords: Anodization; Interface; Osseointegrated implants; Reverse polarization; TiO2 nanotubes